Loss of ceramide synthase 3 causes lethal skin barrier disruption - Jennemann, Richard; Gorgas, Karin; Dalpke, Alexander; Kirsch, Joachim; Nickel, Walter (Human molecular genetics, 2012)
Abstract. The stratum corneum as the outermost epidermal layer protects against exsiccation and infection. Both the underlying cornified envelope (CE) and the